Description of a new species of Chrysobrycon (Characiformes: Stevardiidae) from the rio Curuá basin expands the distribution of the genus to the lower Amazon basin, Brazil - Cárlison Silva-Oliveira; James A. Vanegas-Ríos; André L. C. Canto; Frank R. V. Ribeiro (Neotropical Ichthyology)
Abstract A new species of Chrysobrycon is described from the lower Amazon basin, Brazil. The new species can be diagnosed from its congeners by the combined presence of the following characteristics: presence of a clear or fully depigmented area located posterior to the humeral blotch, which separates it from the longitudinal band of chromatophores along the body flank; 14–16 gill rakers on the first branchial arch; 15–19 dentary teeth; reduced or absent fourth infraorbital; 4–7 maxillary teeth; presence of a terminal lateral-line tube between the caudal-fin rays 10 and 11; 4–5 neural spines between the posteriormost supraneural and the anteriormost dorsal-fin pterygiophore. An identification key to the species of Chrysobrycon is provided. The finding of this new species of Chrysobrycon expands the distribution of the genus to northeastern South America, between ca. 1,000 km from where is known its geographically closer congeners. Furthermore, the description of the new species constitutes the first record of Chrysobrycon in the lower Amazon basin in Brazil.